Description of the larva of Archilestes exoletus (Hagen in Selys) (Odonata: Lestidae) - Dalzochio, Marina Schmidt; Rodrigues, Marciel Elio (Zootaxa, 2011)
The larva of Archilestes exoletus (Hagen in Selys, 1862) is described and illustrated based on exuviae of reared larvae collected in Cascavel, State of Paraná, Brazil. The larva of A. exoletus can be distinguished from other species of Archilestes of which the larva has been described by the absence of a lateral spine at the margin of the 4 th abdominal segment and having the cleft of the ligula closed.